Studi Tentang Pendekatan Pengkajian Keperawatan Yang Efektif Dalam Proses Keperawatan di Ruang Bedah RSUD Dr. Soetomo Surabaya - Nuh Huda, - (2002)
Nursing assessment is the most important component in the nursing process because it will be basic for the nurse during doing nursing care. Nursing assessment may establish successfully nursing process continued. The objective of this study was to identify effectively of Review of System nursing assessment approach and nursing assessment approach that used in the surgical ward of RSUD Dr. Soetomo Surabaya.